Drug-coated balloon used to treat in-stent restenosis of the renal artery - Jaldin, Rodrigo Gibin [UNESP] (2018)
During recent years, drug-coated balloons (DCBs) have emerged as a promising therapeutic option. DCBs directly transfer antiproliferative drugs to the arterial wall in order to decrease myointimal hyperplasia. We describe a case of de novo renal artery in-stent restenosis (ISR) treated with drug-coated balloon angioplasty with acceptable short-term results, achieving blood pressure control using fewer antihypertensive agents. The experience and results obtained with DCBs in other territories could suggest and justify use of this technology in renal artery ISR.